Geriatric Emergency Medicine (Springer International Publishing, 2018)
This book discusses all important aspects of emergency medicine in older people, identifying the particular care needs of this population, which all too often remain unmet. The up-to-date and in-depth coverage will assist emergency physicians in identifying patients at risk for adverse outcomes, in conducting appropriate assessment,and in providing timely and adequate care. Particular attention is paid to the commonpitfalls in emergency management andmeans of avoiding them. Between 1980 and 2013, the number of older patients in emergency departmentsworldwide doubled. Compared with younger patients, older people suffer from more comorbidities, a higher mortality rate, require more complex assessment and diagnostic testing, and tend to stay longer in the emergency department. This book, written by internationally recognized experts in emergency medicine and geriatrics, not only presents the state of the art in the care of this population but also underlines the increasing need for adequate training and development in the field.